Pengaruh Persepsi Siswa tentang E-Book dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran KMPLB Siswa Kelas XI MPLB di SMK Negeri 1 Karanganyar - Aura Widia Mona Magani; Patni Ninghardjanti (Politeknik Kampar, 2024)
This research aims to (1) determine the influence of students' perceptions of e-books on student learning outcomes (2) determine the influence of learning motivation on student learning outcomes (3) determine the influence of students' perceptions of e-books and learning motivation together on outcomes student learning. This research is a quantitative study with a population of 71 class XI MPLB students taking KMPLB subjects at SMK Negeri 1 Karanganyar. As for the sample, a sampling technique was used, namely a non-probability sampling technique with a saturated sample method. Data collection was carried out by distributing research questionnaires. The data analysis technique uses the multiple linear regression analysis method with the help of IBM spss version 23 software. The research results prove that: (1) there is a positive and significant influence on student perceptions of e-books on student learning outcomes. This is proven by the value of tcount (2.887) > ttable (1.995) and the significance value (2) that there is a positive and significant influence of learning motivation on student learning outcomes. This is proven by the value of tcount (5.599) > ttable (1.995) and the significance value (3) that there is a positive and significant influence on students' perceptions of e-books and learning motivation together on student learning outcomes. This is proven by Fcount (56.291) > Ftable (3.130). The results of this study show that the effective contribution value collectively is , while the remaining amount is influenced by other factors not examined in this study.